2020
DOI: 10.1002/cbf.3441
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high glucose on the biological characteristics of nucleus pulposus‐derived mesenchymal stem cells

Abstract: Diabetes mellitus (DM) is a dependent risk factor in the progression of intervertebral disc degeneration (IVDD). High glucose supply has negative effects on nucleus pulpous (NP) cell and mesenchymal stem cell (MSC) biology. However, the effect of hyperglycaemia on the biological characterization of nucleus pulpous-derived mesenchymal stem cell (NPMSC) has not been investigated previously. Therefore, further exploration of the effects of DM-associated hyperglycaemia on NPMSC biology is important to better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…Previous work has clearly demonstrated that diabetes is associated with more rapid IVDD progression (X. Liu et al, 2018). Hyperglycemia‐induced AGE accumulation within the IVD has also been shown to elevate the risk of NPC dysfunction (Y. Liu et al, 2020; Tsai et al, 2014), and diabetic NPCs have been found to exhibit poorer survival and enhanced ECM degradation following AGE exposure (Song et al, 2017; Tsai et al, 2014). The specific mechanisms whereby AGEs modulate NPC functionality, however, have not been well‐defined in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has clearly demonstrated that diabetes is associated with more rapid IVDD progression (X. Liu et al, 2018). Hyperglycemia‐induced AGE accumulation within the IVD has also been shown to elevate the risk of NPC dysfunction (Y. Liu et al, 2020; Tsai et al, 2014), and diabetic NPCs have been found to exhibit poorer survival and enhanced ECM degradation following AGE exposure (Song et al, 2017; Tsai et al, 2014). The specific mechanisms whereby AGEs modulate NPC functionality, however, have not been well‐defined in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that medium with high glucose concentration within a certain range could effectively improve the proliferation ability of MSCs [23,24]. However, some studies also have shown that medium with high glucose might accelerate cell senescence and apoptosis in seveal pathways [25][26][27]. Yanan Kong et al cultured MSCs with high glucose (33 mmol/L) medium, and found that the apoptosis rate of cells remained low after culturing for 1 day, while the apoptosis rate of cells increased greatly after culturing for 5 days [25].…”
Section: Discussionmentioning
confidence: 99%
“…Tzu-Ching C et al cultured BMSCs with low glucose (5.5 mmol/L) and high glucose (25 mmol/L) medium respectively, they also found that high glucose could accelerate the senescence of BMSCs by promoting their ability of autophagy after culturing for 2 weeks [26]. Yang Liu et al cultured nucleus pulposus derived MSCs (NPMSCs) with low glucose (5.5 mmol/L) and high glucose (25 mmol/L) medium respectively, and they found that high glucose medium cultured NPMSCs showed signi cantly decreased expression levels of stemness genes, related mRNA and protein, whereas increased expression levels of cell senescence markers and caspase-3 [27]. Cramer et al applied medium with different concentration glucose (5.56mmol/L, 13.9mmol/L, 27.8mmol/L and 55.6mmol/L) to culture adipose derived stem cells (ADSCs) for 120 hours, and found that the hyperglycemia microenvironment could simultaneously reduce the proliferation ability of ADSCs and increase their apoptosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies under normoxic culture conditions support that high glucose concentration (5000 mg/L) in the culture media can suppress proliferation of bone marrow [ 46 , 47 , 48 ], Bichat’s buccal fat pad [ 49 ] and nucleus pulposus MSCs [ 50 ], reduce their colony forming ability [ 50 ], induce cellular senescence [ 47 , 50 , 51 ], alter MSC spindle-shape morphology [ 47 ], and upregulate autophagy [ 50 , 51 ], compared with low glucose (1000 mg/L) media concentration. In addition, MSCs cultured in low glucose media have been shown to maintain their differentiation capacities and stemness [ 46 , 47 , 50 ], and increase antioxidant enzyme expression and mitochondrial respiration [ 47 ]. In contrast with these results, a few studies have reported that high glucose does not have an effect on the apoptosis and proliferation rates of adipose-derived [ 52 ] and primary BM-MSCs [ 53 ], while it can significantly enhance proliferation of telomerase-immortalized MSCs.…”
Section: Glucosementioning
confidence: 99%